2022
DOI: 10.1089/dia.2021.0542
|View full text |Cite
|
Sign up to set email alerts
|

Automated Insulin Delivery with SGLT2i Combination Therapy in Type 1 Diabetes

Abstract: Background: Use of sodium-glucose cotransporter 2 inhibitors (SGLT2i) as adjunct therapy to insulin in type 1 diabetes (T1D) has been previously studied. In this study, we present data from the first free-living trial combining low-dose SGLT2i with commercial automated insulin delivery (AID) or predictive low glucose suspend (PLGS) systems. Methods: In an 8-week, randomized, controlled crossover trial, adults with T1D received 5 mg/day empagliflozin (EMPA) or no drug (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Garcia-Tirado et al [ 106 ] compared the use of EMPA versus no use in an AID or a PLGM setting. In both types of technical treatment, the intervention group had a significant higher TIR compared to no EMPA while the AID arm had a higher TIR also without the drug (PLGM 80% vs. 63%, +16.5%; p < 0.001; AID 81% vs 71% +9.9% p = 0.04) But also in this “protected” setting of a clinical trial one euDKA occurred.…”
Section: Automated Insulin Delivery Systemmentioning
confidence: 99%
“…Garcia-Tirado et al [ 106 ] compared the use of EMPA versus no use in an AID or a PLGM setting. In both types of technical treatment, the intervention group had a significant higher TIR compared to no EMPA while the AID arm had a higher TIR also without the drug (PLGM 80% vs. 63%, +16.5%; p < 0.001; AID 81% vs 71% +9.9% p = 0.04) But also in this “protected” setting of a clinical trial one euDKA occurred.…”
Section: Automated Insulin Delivery Systemmentioning
confidence: 99%
“…In particular, a study of longer duration may have been required to see incidents of ketosis or diabetic ketoacidosis, as was seen in a similar open-label trial using empagliflozin 5 mg as an adjunct to automated insulin delivery, where one case of ketoacidosis was observed. 11 Dedicated future qualitative studies would thus be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,9 Short studies, however, have shown that SGLT inhibitors as an adjunct to this technology can increase time in the target range with reduced insulin requirements and without increasing hypoglycemia. 10 -12…”
Section: Introductionmentioning
confidence: 99%
“…A recently published free-living, placebo-controlled, cross-over study of 8 weeks duration investigating 5 mg of empagliflozin as an adjunct to advanced continuous subcutaneous insulin infusion (CSII) therapy, using either an automated insulin delivery (AID) system or a predictive low glucose suspend (PLGS) system in 39 individuals with T1D, demonstrated a significantly improved time in glycemic range in both trial arms (AID: time in glycemic range was 81% with empagliflozin versus 71% without empagliflozin; PLGS: 80% versus 63%). The risk of hypoglycemia was comparable; DKA occurred in one participant receiving empagliflozin and this was associated with a nonfunctioning insulin pump [76].…”
Section: Sglt1/2 Inhibitorsmentioning
confidence: 96%